Comparative study between interlocking nail and V-nail in management of fracture shaft tibia - Pathak, Ritesh; Naser, M. A. (International Journal of Research in Orthopaedics, 2018)
Background: Tibia is the most commonly fractured long bone in the body. Interlocked nails, either reamed or unreamed, has become the established method of treatment of closed and Grade I, II and III A open fractures of diaphysis of tibia. The cephalo-medullary nail like V-nail, has advantages of less surgical time and cost effectiveness while disadvantage of rotational instability. The present study was undertaken to compare the short-term as well as long-term results of treatment of diaphyseal fractures of tibia with interlocked nail and V-nail. Methods: Forty patients with fracture of shaft tibia were treated with either interlocked nail or V-nail. Twenty patients were treated with interlocked nail while remaining twenty were treated with V-nail. The follow-up period ranged from 14 weeks to 10 months. The results were assessed according to Ekland grading. Results: In interlocking series, 85% patients had excellent and good result while 15% patients had fair and poor results. In V-nail series, 30% patients had excellent result, 70% patients had good and fair results while no patient had poor result. Conclusions: From our study we conclude that closed interlocked nailing is the most ideal method of management of fracture shaft tibia of all types, allowing early mobilization. Closed V-nail is a simple and short procedure with satisfactory results, when used in simple and unifocal fracture types.